MEASUREMENT OF LDL CHOLESTEROL LEVELS IN A SPECIES WITH HDL PATTERN - Osorio, José Henry (2013)
The methods used for lipid profile measurement in humans, a species with LDL (“Low-density lipoprotein”) pattern, can be unsuitable for the lipid profile determination in species with HDL (“High-density lipoprotein”) pattern. The objective of this study was to compare the precipitation method and the Friedewald method for the measurement of LDL cholesterol in a species with HDL pattern. Blood samples were collected after 24 h fasting in 200 horses of different ages and without discrimination by sex. After serum extraction, levels of LDL cholesterol were determined by both methods. The values obtained by the precipitation method were 32 ± 8.8 mg/dl and for the Friedewald method were 29 ± 7.7 mg/dl (p<0.05). Given the difference in values between methods, it is recommended the Friedewald method for determining levels of LDL cholesterol in the horse, a species with HDL pattern.